How Language Influences Conceptualization : From Whorfianism to Neo-Whorfianism = Kako jeziku utječe na koceptualizaciju : od whorfijanizma do neowhorfijanizma - Štrkalj Despot, Kristina (2021)
Do speakers of different languages think alike because of the universality of the experience of being human or do we all think differently because of differences in our languages? The answer to these questions has changed throughout the history of linguistic thought, ranging from observing languages merely as tools for expressing our thoughts to strongly believing that languages shape and even constrain our thoughts. This paper presents an overview of two most important theories that deal with these questions: the "rise and fall" of linguistic determinism (Whorfianism), and the development of its more cautious version – linguistic relativism (Neo-Whorfianism) – advocated today primarily within the framework of cognitive views of language, as well as their criticisms, most commonly within the framework of generative views of language.
Razmišljaju li govornici različitih jezika jednako zbog univerzalnosti ljudskoga iskustva ili razmišljamo drukčije zbog razlika u našim jezicima? Odgovor na to pitanje mijenjao se tijekom povijesti lingvističke misli u rasponu od promatranja jezika samo kao alata za izražavanje naših misli do uvjerenja da jezik oblikuje, pa čak i ograničava naše misli. U ovome radu daje se pregled dviju najvažnijih teorija koje se bave tim pitanjima: predstavlja se "uspon i pad" jezičnoga determinizma (whorfijanizma) i razvoj njegove opreznije inačice – jezičnoga relativizma (neowhorfijanizma) – koji se danas zagovara u prvome redu unutar okvira kognitivnih pogleda na jezik. Daje se i pregled najvažnijih kritika obaju pogleda, najčešće iz pozicije generativnih pogleda na jezik.
Bibliografija
Summary.